Implementation of the MOORA Method in the Library Book Procurement Decision Support System - Firmansyah, Ferdian; Hakim, Lutfi; Kristanto, Sepyan Purnama (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Every year, the library must be buying books in order to increase the collection of books that are in the libraries. When purchasing books, it is necessary to make various considerations so that the books that will be used are relevant to the needs of students and lecturers in academic activities. The procurement of books in the library is still done manually with book selection carried out by the librarians is still one-on-one of the list of submissions of books that have been made by the lecturer. Therefore, there is a need to have a renewal of the system of book acquisition in the libraries one of which uses the decision support system in the process of the book acquisitions. In this study the decision support system used is the MOORA method in determining the rating of the recommendation book to be held. The alternative submission data will be obtained from the library's proposal with the book data from the publisher's book collection. The study uses five criteria for book acquisition, including book price, year of publication, book stock, number of book proposals, and availability of books. This decision support system will provide a recommendation for purchase of books from the alternative data for book submission that will be calculated using the MOORA method to obtain any book recommendation that matches the criteria and budget of the book procurement. Accuracy level testing using the Confusion Matrix by comparing the results of manual calculations with the system to obtain 100% accuracy.